Peningkatan Hasil Belajar melalui Permainan Snake and Ladder dalam Meningkatkan Kemampuan Berbicara Bahasa Inggris Siswa Kelas IX-A UPT SMP Negeri 1 Tellu Limpoe Kabupaten Sidenreng Rappang - Marsuni (Kilau Publishing, 2024)
The English speaking ability of students in Class IX-A at UPT SMP Negeri 1 Tellu Limpoe, Sidenreng Rappang Regency, still seems to show a low level of skill from year to year. This can be identified through various indicators, such as difficulties in expressing ideas orally in English that often stop in the middle of the conversation. The purpose of this study is directed to create a more interactive, fun, and effective learning atmosphere by applying the Snake and Ladder Game to improve speaking skills so as to increase students' learning motivation as well as their learning outcomes in speaking English. This research was conducted in class IX-A UPT SMP Negeri 1 Tellu Limpoe Sidenreng Rappang Regency with the number of students in the research class was 27 students. The Research Method conducted in the study was Classroom Action Research (CAR). The results showed that process assessment, reflection, and discussion as well as discussion of research, it was concluded that snake and ladder was able to improve speaking skills in English Class IX-A UPT SMP Negeri 1 Tellu Limpoe Sidenreng Rappang Regency, as evidenced by student activity during cycle I and cycle II learning increased gradually, student response to the learning process was very good, and there was an increase in mastery of speaking compared to before. It can be seen that student learning completeness in cycle I reached 70% and in cycle II reached 100%.